2022
DOI: 10.3389/fonc.2022.1054885
|View full text |Cite
|
Sign up to set email alerts
|

Unmet supportive care needs and associated factors: Evidence from 4195 cancer survivors in Shanghai, China

Abstract: BackgroundCancer survivors at different stages of life often have different needs that make it challenging for services to provide satisfactory care. Few studies have considered whether services are truly meeting the needs of cancer patients by exploring and identifying their perspectives on unmet needs.ObjectiveThe aim of this study was to identify the unmet needs of cancer survivors and to further determine the potential impact of socio-demographic factors.MethodsA cross-sectional study that included 4195 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
3
4
1
Order By: Relevance
“…However, this effect diminishes upon adjusting for potential confounding variables using a multivariate regression model. This contradicts with previous empirical evidence suggesting a strong correlation between the time since diagnosis and greater supportive care needs [33,34]. Additionally, and in the context of our study's findings, it is noteworthy to discuss the significant independent association observed between singlehood and psychological need scores among childhood cancer survivors.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, this effect diminishes upon adjusting for potential confounding variables using a multivariate regression model. This contradicts with previous empirical evidence suggesting a strong correlation between the time since diagnosis and greater supportive care needs [33,34]. Additionally, and in the context of our study's findings, it is noteworthy to discuss the significant independent association observed between singlehood and psychological need scores among childhood cancer survivors.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous reports suggested similar findings in adults and AYA groups [34][35][36][37]. This relationship, marginally significant on conventional levels, might be suggestive of a transition point where adult survivors of childhood cancer start to face increased difficulties navigating healthcare systems and require more information about their health and care.…”
Section: Discussionsupporting
confidence: 70%
“…Fear of cancer recurrence (FCR) could be a powerful determinant of physical symptoms [104], psychological distress [105] and quality of life [106]. Our study demonstrated that breast cancer patients not only faced the huge unmet need in FCR regarding "fears cancer spreading/recurrence", but also in "dealing with the impact that having a faulty gene has had on your family", which could be similarly re ected in high information need related to Information needs were proved to be the most important concern among the diverse unmet needs of cancer survivors [109]. Anxiety related to inadequate information support is common among breast cancer patient.…”
Section: Prevalence Of Unmet Needmentioning
confidence: 78%
“…There is a huge burden of supportive care needs among BCSs that are still under management, such as psychosocial issues [ 108 ], sexuality [ 109 ], information [ 110 ], and symptoms burden [ 111 ]. Most authors have investigated the USCNs among BCSs [ 112 , 113 ] through cross-sectional study or qualitative interview. However, to our knowledge, few researchers conducted evidence synthesis [ 23 , 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…Information needs were proved to be the most important concern among the diverse USCNs of cancer survivors [ 113 ]. Among BCSs, anxiety related to inadequate information support is common.…”
Section: Discussionmentioning
confidence: 99%